Association of Ventricular Arrhythmias With Dementia: The Atherosclerosis Risk in Communities (ARIC) Study - Norby, Faye L. (Neurology, 2021)
OBJECTIVE: We performed a cross-sectional analysis to determine whether nonsustained ventricular tachycardia (NSVT) and premature ventricular contractions (PVCs) were associated with dementia in a population-based study. METHODS: We included 2,517 (mean age 79 years, 26% Black) participants who wore a 2-week ambulatory continuous ECG recording device in 2016 to 2017. NSVT was defined as a wide-complex tachycardia ≥4 beats with a rate >100 bpm. We calculated NSVT and PVC burden as the number of episodes per day. Dementia was adjudicated by experts. We used logistic regression to assess the associations of NSVT and PVCs with dementia. RESULTS: The mean recording time of the Zio XT Patch was 12.6 ± 2.6 days. There were 768 (31%) participants with NSVT; prevalence was similar in White and Black participants. There were 134 (6.5%) dementia cases (5% in White, 10% in Black participants). After multivariable adjustment, there was no overall association between NSVT and dementia; however, there was a significant race interaction (p < 0.001). In Black participants, NSVT was associated with a 3.67 times higher adjusted odds of dementia (95% confidence interval [CI] 1.92–7.02) compared to those without NSVT, whereas in White participants NSVT was not associated with dementia (odds ratio [95% CI] 0.64 [0.37–1.10]). In Black participants only, a higher burden of PVCs was associated with dementia. CONCLUSIONS: Presence of NSVT and a higher burden of NSVT and PVCs are associated with dementia in elderly Black people. Further research to confirm this novel finding and to elucidate the underlying mechanisms is warranted.